PENYULUHAN LINGKUNGAN SEHAT DAN CARA MENGATASI SAMPAH RUMAH TANGGA DI RW 05 CISASAWI, CIHANJUANG, JAWA BARAT : Healthy Environment Counseling and How to Overcome Househould Waste in RW 05 Cisasawi, Cihanjuang, West Java - Lusi Marlina; Ratna Wulandari; Ade Yuliana; Reni Listiana; Asmat Purba (PUAN INDONESIA, 2023)
The environmental conditions and problems found in RW 05 Cisasawi Village, Cihanjuang are garbage. The final disposal of waste in Cisasawi village is still unclear and is often constrained by the distribution of waste. This requires good management regarding waste disposal in Cisasawi village, especially RW 05. The management carried out is community-based management, so that people are aware of a healthy and clean environment. Provision of trash bins around the neighborhood of RW 05 Cisasawi Village is the first step in an effort to raise public awareness in waste management. The next activity was outreach to PKK women and village officials in RW 05 Cisasawi Village. The people of RW 05 Cisasawi Village are interested in waste management through the Garbage Bank and the use of waste for composting.